Perbedaan Asal Media Penukar Ion untuk Menurunkan Kesadahan Air Sumur Gali - Dike Fitriana; Herman Santjoko; Mohamad Mirza Fauzie (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
One of compulsory chemical parameters of water for sanitation and hygiene needs is hardness (CaCO3). One method to reduce water hardness is by ion exchanging This study used natural zeolite from Gedang Sari, Gunung Kidul; bentonit from Nanggulan, Kulon Progo, and zeolite from a chemical store. The study was a true experiment with one group pre-test post-test design, and was conducted in June and July 2018. The hard water samples were taken from Wonotawang Village RT 11 of Bangunjiwo, Kasihan, Bantul. The water treament were held in nine replications.The data were analyzed by using one way analysis of variance at 95 % confidence level.Descriptively, the average of hardness reduction yielded from Gunung Kidul’s zeolites was 50,90 %, from Kulon Progo’s Bentonite was 66,11 %, and from zeolite of chemical store was 56,19 %. Statistical analysis produced a p-value of 0,037 which means that in filtration process the three medias have significant different ability in reducing water hardness.